Advection–diffusion settling of deep-sea mining sediment plumes. Part 2. Collector plumes. (19th August 2022) - Ouillon, Raphael; Muñoz-Royo, Carlos; Alford, Matthew H.; Peacock, Thomas
Abstract: Abstract : We develop and investigate an advection–diffusion-settling model of deep-sea mining collector plumes, building on the analysis of midwater plumes in Part 1. In the case of collector plumes, deposition plays a predominant role in controlling the mass of sediment in suspension, and thus on setting the extent of the plume. We first discuss the competition between settling, which leads to deposition, and vertical turbulent diffusion, which stretches the plume vertically and reduces deposition. The time evolution of the concentration at the seabed is found to be a highly nonlinear function of time that depends non-trivially on the ratio of diffusion to settling time scales. This has direct implications for the three extent metrics considered, namely the instantaneous area of the seabed where a deposition rate threshold is exceeded, the furthest distance from the discharge where the plume exceeds a concentration threshold and the volume flux of fluid in the water column that ever exceeds a concentration threshold. Unlike the midwater plume, the particle velocity distribution of the sediment has the greatest influence on the extent metrics. The turbulence levels experienced by the plume also markedly affects its extent. Expected variability of turbulence and particle settling velocity yields orders of magnitude changes in the extent metrics.